Valoración de la postura corporal en relación al peso de la mochila en escolares de la Unidad Educativa Manuel Ygnacio Monteros Valdivieso. - Guerrero Moreno, Inés Dalila (2017)
The present investigation has as objective: To determine alterations of the body posture in relation to the weight of the backpack in schoolchildren of the Manuel Ygnacio Monteros Valdivieso Educational Unit. Materials and methods: a quantitative, descriptive and cross-sectional study was conducted between March and August of 2016. The sample was constituted by 146 students from 6 to 11 years of age. A previously validated pilot survey for schoolchildren was carried out, in addition to a physical examination by applying the Adams test and the sagittal arrow test. The following results were obtained: 71.2% carried a backpack weighing more than 10% of body weight; in this same population it was found that 84.62% moves around walking and that 65.06% had fatigue; while 70.19% referred to pain at the shoulder with a level of frequency of 3 to 4 times per week with an intensity of 4 in addition; on physical examination, 56.7% presented hyperkyphosis, thus contrasting with an excessive weight that the backpack gives, may contribute to the appearance of discomfort and of postural alterations. KEY WORDS: Alteration of the spine, backpack, hyperkyphosis, pain, tiredness.